2021
DOI: 10.1051/bioconf/20212901006
|View full text |Cite
|
Sign up to set email alerts
|

On the choice issue of functional tests in physical fitness of the undergraduates

Abstract: Purpose: The purpose of our research is to determine, on the basis of mathematical processing of the experimental results, the most informative functional test, which makes it possible with a greater degree of reliability to assess the state of the vestibular apparatus and the presence of deviations in the work of the nervous system of students of higher educational institutions, and thereby recommend it for use in the practice of physical education in higher educational institutions. Results: Data analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…To exclude the gap between school requirements to the level of knowledge, skills, and abilities and "entrance" indicators of physical culture and sports, the university standards of physical training for first-year students meet school standards [20,21].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To exclude the gap between school requirements to the level of knowledge, skills, and abilities and "entrance" indicators of physical culture and sports, the university standards of physical training for first-year students meet school standards [20,21].…”
Section: Methodsmentioning
confidence: 99%
“…Analysis of scientific and academic literature on the issues of formation of general competences of students of general education institutions and universal competences of university students in physical culture and sports was performed. It showed that most firstyear university students cannot meet the requirements of higher education establishments in the physical culture and sports owing to an improper level of theoretical, methodical and physical training [19][20].…”
Section: Introductionmentioning
confidence: 99%